De l’État au citoyen, redistribution des cartes : éléments d’une histoire de la cartographie - Élisabeth Habert (Revue d'ethnoécologie)
Maps are very powerful visual instruments which have caused strong enthusiasm way beyond the expert community with professional geographers and mapmakers. The profusion of maps raises questions on their use as well as on mapmakers’ training with regards to the new digital stakes and the development of participatory projects. Since the late 1980s, participatory mapping has become an essential tool for development assistance programs. The expression “participatory mapping” has developed over the last ten years and today the term “neocartography” is used and acknowledged by the ICA (International Cartographic Association) to qualify this mapmaking process. These participatory maps give tangible forms to invisible realities on traditional thematic maps; they locate places that are meaningful to communities (non-permanent and informal facilities) and are not limited to presenting information about geographic characteristics. They illustrate information about the use of land, the mythology, the local customs, the know-how, the rituals, often difficult to include and analyze in a geo-referenced database.